Discourse Analysis on the Constitutional Court Exception News Allowing Gibran to Run in Presidential Election - Gunawan, Rizki (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
The study entitled Discourse Analysis on the Indonesian Court Exception News Allowing Gibran to Run in the Presidential Election is a Critical Discourse Analysis (CDA) of how British newspapers, i.e., Reuters and The Guardian reported what the Constitutional Court (Mahkamah Konstitusi/MK) issued on the eligibility criteria for the president and vice president. The study is aimed at elaborating on the discourse side of the news articles by using Norman Fairclough's CDA with three dimensions: text analysis, discourse practice analysis, and social analysis. This study applies descriptive research by understanding the article and reading other supporting information. The linguistic study can be linked to the social analysis by the last element of CDA, which is sociocultural analysis. This explains the result of text analysis and discourse practice in the news report which mostly describes the controversy and impact of the court’s decision that ruled that candidates under the required age of 40 could seek the presidency or vice presidency in the 2024 election, provided they have previously held elected regional office. The study provides insights into how British newspapers framed and interpreted the Indonesian Constitutional Court's decision on presidential candidacy eligibility, highlighting implications for media representation and public discourse.